Effects of exercise mode and participant sex on measures of anaerobic capacity - Hill, D. W.; Vingren, J. L. (The Journal of Sports Medicine and Physical Fitness, 2014)
AIM: The purpose of this study was to compare values of maximal accumulated oxygen deficit (MAOD; a measure of anaerobic capacity) and peak post-exercise blood lactate concentration ([lactate]; a reflection of glycolytic contribution) in running and cycling, in women and men.